2015
DOI: 10.1158/1940-6207.capr-14-0089-t
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of HPV16-Positive Oropharyngeal Cancer in Black Patients Over Time: University of Maryland 1992–2007

Abstract: While we previously reported a striking racial difference in the prevalence of human papillomavirus (HPV) positive oropharyngeal cancer (OPSCC), less is known about differences in outcomes and trends over time in OPSCC by HPV status and race. We conducted a retrospective analysis of 467 OPSCC patients treated at the University of Maryland Greenebaum Cancer Center between 1992 and 2007, of which 200 had tissue available for HPV16 testing. HPV16 positive patients were significantly more likely to be white, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 28 publications
5
51
1
Order By: Relevance
“…Similar to findings across study populations (Betiol et al 2013;Chaturvedi et al 2008;Ryerson et al 2008), the majority of HPV types within NCDB were type 16 or types 16/18 combined. Studies have shown a higher incidence of HPV-related HNSCCs in nH whites than in nH blacks (Jiron et al 2014;Settle et al 2009;Zandberg et al 2015), and the majority of HPV-related cases within our study were among nH whites. Our analysis of a subset of cases from 2004 to 2012 demonstrated a higher incidence of HPV-related tumors among nH white males in oropharyngeal and non-oropharyngeal site groups, in local and distant stages, and across all grade categories, except for well-differentiated tumors.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Similar to findings across study populations (Betiol et al 2013;Chaturvedi et al 2008;Ryerson et al 2008), the majority of HPV types within NCDB were type 16 or types 16/18 combined. Studies have shown a higher incidence of HPV-related HNSCCs in nH whites than in nH blacks (Jiron et al 2014;Settle et al 2009;Zandberg et al 2015), and the majority of HPV-related cases within our study were among nH whites. Our analysis of a subset of cases from 2004 to 2012 demonstrated a higher incidence of HPV-related tumors among nH white males in oropharyngeal and non-oropharyngeal site groups, in local and distant stages, and across all grade categories, except for well-differentiated tumors.…”
Section: Discussionsupporting
confidence: 41%
“…The higher incidence of more advanced and aggressive HNSCCs among nH black males at the time of diagnosis likely contributes to their survival disadvantage relative to nH white males. HPV-related HNSCCs have a significantly better prognoses than those associated with smoking and alcohol (Zandberg et al 2015), and the racial differences in HPV observed in NCDB cases may also partly explain the survival disadvantage observed in nH black males (Gourin and Podolsky 2006;Shiboski et al 2007;Zandberg et al 2014). Future studies are needed to better understand the factors that contribute to racial differences in primary anatomical site, stage, and factors associated with HPV-related HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In addition, DNA was extracted from FFPE tissue of 13 de-identified cervical cancer cases, also using the QIAamp DNA FFPE Tissue Kit. Following institutional review board (IRB) approval, all tumor samples were obtained from the University of Maryland Greenebaum Cancer Center (UMGCC) Pathology and Biorepository shared service.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…19 DNA was extracted from several (3-5) 10 m sections of FFPE oropharyngeal cancer tissue using the QIAamp DNA FFPE Tissue Kit (Qiagen), according to the manufacturer's protocol. DNA was quantified using the Quant-iT dsDNA Assay Kit, High Sensitivity (Invitrogen, Thermo Fisher Scientific, Grand Island, NY, USA), and stored at 280°C in aliquots.…”
Section: Hpv16 Pcrmentioning
confidence: 99%